Abnormal twin-twin interaction in an Mg-3Al-1Zn magnesium alloy processed by laser shock peening. (May 2019) - Mao, Bo; Liao, Yiliang; Li, Bin
Abstract: Twin-twin interaction in an Mg-3Al-Zn1 magnesium alloy subjected to ultra-high strain rate deformation (~10 6 /s) was investigated. The material was processed by laser shock peening and the microstructure at various depths was characterized by electron backscattered diffraction. The results show that different 10 1 ¯ 2 twin variants were activated in individual parent grains, and the interfaces between these twin variants present very abnormal morphologies. One variant can be totally surrounded by the other, forming isolated or disconnected islands which have the same crystallographic orientation. A mechanism was proposed to account for the abnormal twin-twin interaction. Graphical abstract: Unlabelled Image